Removal of metal ions from electrochemical decontamination solution using organic acids - Naznin, Marufa; Choi, Jiyeon; Shin, Won Sik; Choi, Jaeyoung (TAYLOR & FRANCIS INC, 2017)
Applicability of the organic acids and cyclodextrin (CD) for the removal of Fe, Co and Ni from the spent electro-decontamination solution was investigated. Oxalic acid showed the highest removal efficiency: 90% for 0.89M Fe and 95% for 0.0089M Co and Ni, respectively. The metal-oxalate precipitates were characterized by differential scanning calorimetry/thermogravimetry analysis (DSC/TGA), Fourier transform infrared (FTIR) and X-ray fluorescence (XRF). After thermal decomposition at >300 degrees C, the metal-oxalate precipitates were transformed into metal oxides (Fe2O3, FeO, CoO and NiO) and pure metals (Co and Ni). The results imply that organic acids have a high potential for the removal of heavy metals from electro-decontamination solutions.
Keywords: TARTARIC ACID; CYCLODEXTRIN CHEMISTRY; SINGLE-CRYSTAL; RECOVERY